AB0309 MEASURING THE DIFFERENCE: COMPARISON OF MEASUREMENT OF FREE INFLIXIMAB ANTI-DRUG ANTIBODIES. (2nd June 2020) - Hamilton, R.; Shields, S.; Mcgucken, A.; Macdonald, J.; Perry, M.; Dunlop, A.; Gribben, E.; Galloway, P.
Abstract : Background: Infliximab (IFX) was one of the first TNF alpha inhibitors to be licenced in inflammatory arthritis and is still commonly used today. Studies have shown that approximately 50% of primary IFX responders will suffer from secondary loss of response within the first 12 months of treatment (1). The development of Anti-Drug Antibodies (ADA's) plays a significant role in this treatment failure (2). Monitoring of ADA's helps identify those patients who fail to respond to treatment due to low IFX trough levels. In this scenario the presence of ADA's can aid decision-making regarding increasing IFX dosing or switching biologic therapy to optimise treatment. (3). Objectives: Despite their potential importance the detection of ADAs varies widely depending on the type of assays used. The aim of this study was to determine the qualitative concordance of three commercially available ELISA kits for measurement of free ADAs to IFX on the Grifols Triturus analyser. Methods: 150 patient samples from patients with inflammatory conditions and low IFX trough drug levels (≤0.6µg/ml) were analysed for free ADAs using Promonitor, Lisa Tracker and IDKmonitor kits on the Grifols Triturus automated ELISA analyser. Results: Kappa coefficient (κ) analysis indicated a moderate agreement between the Promonitor and IDKmonitor assays (κ =0.484 (95% CI, 0.357 to 0.611)) and the IDKmonitor and Lisa Tracker assays (κ = 0.485 (95% CI, 0.348-0.621)) as well as substantial agreement between the Promonitor and Lisa Tracker assays (κ =0.768 (95% CI, 0.667-0.870)). Figure 1 shows the distribution of samples identified as free ADA positive by each kit. Conclusion: All kits appear amenable for utilisation in a high-throughput laboratory though a true quantitative comparison between these kits was precluded by the absence of any certified reference material for free ADAs to IFX. Although broad qualitative agreement was found between the three kits, they should not be used interchangeably for patient management. Further research is required to estimate the impact of free ADAs on efficiency of IFX treatment and patient management. References: [1]Quistrebert J, Hässler S, Bachelet D et al. Incidence and risk factors for adalimumab and infliximab anti-drug antibodies in rheumatoid arthritis: A European retrospective multicohort analysis . Seminars in Arthritis and Rheumatism Volume 48, Issue 6, June 2019, Pages 967-975 2. [2]Moots RJ, Xavier RM, Mok CC, Rahman MU, Tsai W-C, Al-Maini MH, et al. (2017) The impact of anti-drug antibodies on drug concentrations and clinical outcomes in rheumatoid arthritis patients treated with adalimumab, etanercept, or infliximab: Results from a multinational, real-world clinical practice, non-interventional study . PLoS ONE 12(4): e0175207. https://doi.org/10.1371/journal.pone.0175207 [3]Smolen JS, Landewé R, Bijlsma J, et al. EULAR recommendations for the management of rheumatoid arthritis with synthetic and biological disease-modifying antirheumatic drugs : 2016 update. Annals of the Rheumatic Diseases 2017;76:960-977. Disclosure of Interests: Rhona Hamilton: None declared, Stephanie Shields: None declared, Andrew McGucken: None declared, Jonathan MacDonald: None declared, Martin Perry Grant/research support from: Grifols, Abbvie, Sandoz unrestricted educational grant, Consultant of: Abbvie, Gilead, Celltrion Advisory Board, Speakers bureau: Sandoz, Allan Dunlop: None declared, Elaine Gribben: None declared, Peter Galloway: None declared